Cover Picture: Maillard Degradation Pathways of Vitamin C (Angew. Chem. Int. Ed. 18/2013). Issue 18 (8th April 2013) - Smuda, Mareen; Glomb, Marcus A.
<x xml:space="preserve">Abstract</x> Even 80 years after the elucidation of the structure of L‐threo‐ascorbic acid (vitamin C), the chemistry of this reactive reducing carbohydrate remains exciting. In their Communication on page 4887 ff., M. A. Glomb and M. Smuda report on their investigations into the Maillard degradation pathway, which revealed three major fragmentation mechanisms that lead to carbonyl and dicarbonyl compounds, carboxylic acids, and amide advanced glycation endproducts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>